1993
DOI: 10.1093/jpepsy/18.4.425
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Disabling Condition Visibility on Family Functioning

Abstract: Examined whether the level of family functioning and the components contributing to adaptive family functioning differed in families of visibly handicapped children (cerebral palsy) when compared to families of nonvisibly disabled children (diabetes). Other factors included effect of disability severity on family functioning, comparison of families of disabled children to families of able-bodied children, and comparison of mothers' and fathers' perceptions of family functioning. The sample comprised 139 two-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…Moreover, families of children with multiple disabilities who had a history of substantiated abuse were compared to nonreported families who had children with disabilities, and no significant differences were found in current stress between the groups (Benedict, Wulff, & White, 1992), Another study reported mean stress scores, both parent-and child-related aspects, comparable to the normative sample (Krauss, 1993). Such findings reflect several authors' interpretation that despite significant stressors, families of children with disabilities adapt and accommodate without significant impact on family functioning (Gallimore, Weisner, Bernheimer, Guthrie, & Nihira, 1993;Kazak & Marvin, 1984;Saddler, Hillman, & Benjamins, 1993).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, families of children with multiple disabilities who had a history of substantiated abuse were compared to nonreported families who had children with disabilities, and no significant differences were found in current stress between the groups (Benedict, Wulff, & White, 1992), Another study reported mean stress scores, both parent-and child-related aspects, comparable to the normative sample (Krauss, 1993). Such findings reflect several authors' interpretation that despite significant stressors, families of children with disabilities adapt and accommodate without significant impact on family functioning (Gallimore, Weisner, Bernheimer, Guthrie, & Nihira, 1993;Kazak & Marvin, 1984;Saddler, Hillman, & Benjamins, 1993).…”
supporting
confidence: 82%
“…Several studies neglected to report the ethnic composition of their study samples, apparently not considering race a pertinent issue (Cameron et al, 1991;Kazak & Marvin, 1984;Krauss, 1993), Many studies report predominantly or entirely Caucasian samples (Beckman, 1983(Beckman, , 1991Boyce et al, 1991;Dyson, 1991Dyson, , 1993Kirkham et al, 1986;McKinney & Peterson, 1987), In addition, those studies reporting the socioeconomic status of their samples describe their samples as middle income or above (e.g., Beckman, 1983Beckman, , 1991Dyson, 1991Dyson, , 1993Gallimore et al, 1993;Saddler et al, 1993). Moreover, studies primarily involve families with two parents present (e.g., Beckman, 1983Beckman, , 1991McKinney & Peterson, 1987;Dyson, 1991Dyson, , 1993Gallimore et al, 1993;Krauss, 1993;Saddler et al, 1993), Some of these authors acknowledge the limitations of interpreting findings due to their sample characteristics (Beckman, 1991;Boyce et al, 1991;Dyson, 1991Dyson, , 1993.…”
mentioning
confidence: 99%
“…1992). Others did not find differences in stress levels of mothers of children with different kinds of disabilities (Saddler et al . 1993; Molteno & Lachman 1996).…”
Section: Resultsmentioning
confidence: 97%
“…For example, a study by Huebner, Thomas, and Berven (1999) showed that there were no main effects of visible disability on attachment and interpersonal characteristics. Saddler, Hillman, and Benjamins ( 1993) found that neither visibility nor the severity of a disability differentially affected family functioning. Levinson and Starling ( I 98 1) found that the level of stigma was not significantly related to the visibility of the child's defect.…”
mentioning
confidence: 95%